Canto Coral, escola de higienização - Costa, Fernando José Monteiro da (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The history of the discipline Canto Coral makes up for a course, rarely, solid and logical, but often according the policies and politicians of the time, not becoming a sort of a development platform. It was, always, more important the growth of the physical body and handicrafts, than the possibility of a true creative freedom, which is postulated by music. But when it is introduced, appears in the features of the hygiene and unison.